Lived Experience of Electronic Sports: A Phenomenological Study of Motivations and Challenges - Ahmadi, Maryam; Majedi , Nima; Hosseini Semnani , Akram Sadat (Journal of Foresight and Health Governance, 2025)
This study was conducted with the aim of exploring the lived experiences of electronic sports (e-sports) players in Iran and providing a phenomenological analysis of their motivations and challenges. The statistical population included active e-sports players in Iran who were selected purposefully using the theoretical sampling method. The inclusion criteria were active experience in this field, willingness to participate in the study, and the ability to articulate personal experiences. In total, 17 participants (4 women and 13 men) with an average age of 25 years and between 4 to 12 years of experience in e-sports were examined. Data were collected through in-depth semi-structured interviews. To ensure credibility and dependability, the trustworthiness criteria proposed by Guba and Lincoln (1985)—including prolonged engagement in the field, persistent observation, triangulation, peer debriefing, and member checking—were applied. Findings revealed that the lived experiences of players can be analyzed across three main dimensions: (1) Lived Experiences (self-concept and identity, emotional experiences, cognitive and skill development, and escapism and role-playing); (2) Motivations for Participation (game appeal and dynamics, social and global interactions, economic and professional opportunities, accessibility and usability, and emotional and motivational effects); and (3) Challenges Encountered (personal challenges, financial and economic barriers, technical and infrastructural problems, social and familial obstacles, and competitive and professional difficulties). The results indicate that electronic sports provide a multidimensional and complex experience for players, which, while offering numerous opportunities, also presents diverse challenges.